Exact Solutions of the Vakhnenko-Parkes Equation with Complex Method. (9th November 2017) - Gu, Yongyi; Yuan, Wenjun; Aminakbari, Najva; Jiang, Qinghua
Abstract : We derive exact solutions to the Vakhnenko-Parkes equation by means of the complex method, and then we illustrate our main results by some computer simulations. We can apply the idea of this study to related nonlinear differential equation.